Amir aur girgit: husnain readers bilingual english & urdu stories (Husnain Lahore, 2020)
Amir and the Chameleon by Husnain Readers is a bilingual story about a young boy named Amir who encounters a fascinating creature, a chameleon. Amir is amazed by the chameleon's ability to change its color to blend with its surroundings. The story explores the concept of camouflage and the wonder of nature, captivating young readers with its engaging narrative and colorful illustrations.